DESIGNING PROJECT AND PROCESS TO FOSTER INTRAPRENEURSHIP COMPETENCE OF EMPLOYEES - Wahyudi, Slamet (NIAGAWAN, 2025)
This research aims to determine the practical model of the intrapreneurship process and project in Muamalat Bank. This research paper was conducted using a qualitative method with a descriptive analysis. In terms of the data collection process, the interview technique was used. Some data were collected, including numerous processes and projects related to intrapreneurship efforts in this Sharia Bank. The novelty of this research is how a Sharia bank increases intrapreneurship competence with the most applicable model. The discussion was analyzed using a design thinking process, including empathizing, defining, ideating, prototyping, and testing. This is to find out the current model used by Muamalat Bank. Intrapreneurship, nowadays known as corporate entrepreneurship, fosters creativity, innovation, and spirit to compete and survive in a tight business competition. The top management of the bank proposes some intrapreneurship activities for its employees. The final goal of this research is the test result of the intrapreneurship model, which was created with the Design Thinking Process earlier. Furthermore, this model will be tested with a CEAI or Corporate Entrepreneurship Assessment Instrument. In general, with Intrapreneurship, business owners will be more confident in doing business as usual. Due to this fact, staff has more creativity and actively contributes to sustainability and the effort to increase the corporation's profit. Especially for this leading Sharia banking, this is one of the efforts to choose in order to be a part of Fortune 100 Indonesia. Keywords: Fortune 100, Sharia Banking, Sustainability, Design Thinking Process, Intrapreneurship Model